2016
DOI: 10.1186/s40064-016-3603-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between TNF-α −857 C/T polymorphism and ankylosing spondylitis susceptibility: evidence from a meta-analysis

Abstract: Certain studies have suggested that the tumor necrosis factor-α (TNF-α) −857 C/T polymorphism is associated with risk of ankylosing spondylitis. However, the conclusions remain controversial. Therefore, we performed a meta-analysis to provide a more precise conclusion. Such databases as PubMed, Embase, CBM, CNKI, and Wanfang Data were searched to identify relevant studies up to August 26, 2015. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the association between TNF-α −857 C/T pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The present study reveals that compared with the CC genotype, the rs1799724 CT genotype is a risk factor for pAIH. Despite conflicting data regarding rs17999724 and autoimmune diseases, the findings agree with meta-analyses of diseases such as ankylosing spondylitis [20], Crohn’s disease [21] and vitiligo [18] using additive, dominant, and allele models. In contrast, a lack of this association was documented for idiopathic nephrotic syndrome [30] and rheumatoid arthritis [31].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study reveals that compared with the CC genotype, the rs1799724 CT genotype is a risk factor for pAIH. Despite conflicting data regarding rs17999724 and autoimmune diseases, the findings agree with meta-analyses of diseases such as ankylosing spondylitis [20], Crohn’s disease [21] and vitiligo [18] using additive, dominant, and allele models. In contrast, a lack of this association was documented for idiopathic nephrotic syndrome [30] and rheumatoid arthritis [31].…”
Section: Discussionsupporting
confidence: 78%
“…Overexpression of TNF-α in AIH patients’ sera has been reported, with the level directly correlating with prognosis [19]. In addition, the TNF promoter polymorphism rs1799724 (c.-1037C > T) has been associated with autoimmune diseases, such as ankylosing spondylitis and Crohn’s disease [20], [21] and with susceptibility to hepatitis B virus infection in some populations [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the potential of miRNAs as biomarkers for different aspects of the epileptogenic process [141,142]. Recent studies have reported that the associations of miRNAs and SNPs, one of which in childhood of epilepsy [143], and the relation to drug-resistance [144]. Here, we show for the first time the number of miRNAs that targeting the CYP2C19 gene, which includes the following: hsa-miR-1270, hsa-miR-455-3p, hsa-miR-4325, hsa-miR-7703, hsa-miR-6880-5p, hsa-miR-6851-5p, hsa-miR-3689d, hsa-miR-4683, hsa-miR-6499-3p, hsa-miR-767-5p, hsa-miR-6134, hsa-miR-4537, hsa-miR-5186, hsa-miR-665, hsa-miR-4459, hsa-miR-92b-3p, hsa-miR-92a-3p, hsa-miR-367-3p, hsa-miR-363-3p, hsa-miR-32-5p, hsa-miR-25-3p, hsa-miR-3180-5p, hsa-miR-3912-5p, hsa-miR-874-3p, hsa-miR-3157-3p, hsa-miR-5195-3p, hsa-miR-145-5p, and hsa-miR-6886-3p.…”
Section: Functional Genomics and Precision Medicinementioning
confidence: 99%
“…TNFi block the activity of TNFα, a key inflammatory mediator as a pro-inflammatory cytokine. Several studies have established a significant relationship between TNFα and AS [4][5][6][7][8]. TNFα is known to play a crucial role in the pathogenesis of AS, as it is overproduced in AS predominantly by active macrophages and T-lymphocytes, playing key roles in the inflammation of spine and sacroiliac joints and extra-articular manifestations including uveitis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…TNFα is known to play a crucial role in the pathogenesis of AS, as it is overproduced in AS predominantly by active macrophages and T-lymphocytes, playing key roles in the inflammation of spine and sacroiliac joints and extra-articular manifestations including uveitis [4,5]. Genetic association studies have evaluated the link between TNFα polymorphisms and susceptibility to AS, indicating a potential genetic influence on the development of the disease [6]. Furthermore, the efficacy of TNFα inhibitors for the treatment of AS has been demonstrated, highlighting the therapeutic relevance of targeting TNFα in managing AS [7,8].…”
Section: Introductionmentioning
confidence: 99%